2000
DOI: 10.1097/00005131-200001000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Recovery Score for Elderly Hip Fracture Patients: I. Development

Abstract: The resulting eleven-item Functional Recovery Score is comprised of three main components: basic activities of daily living (BADL) assessed by four items, instrumental activities of daily living (IADL) assessed by six items, and mobility assessed by one item. Basic activities of daily living comprise 44 percent of the score; instrumental activities of daily living comprise 23 percent, and mobility comprises 33 percent. Complete independence in basic and instrumental activities of daily living and mobility resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 9 publications
2
56
0
4
Order By: Relevance
“…Based upon the nature of the health care delivery system in our city, virtually all patients initially operated upon at our institution who underwent a reoperation for their hip fracture for any reason would be treated again at our institution. It is well-recognised [1,31] that elderly patients represent a difficult patient population to return for routine follow-up. Since our only outcome measures were the immediate postoperative position of the screw or blade and reoperation and cut-out rates within the first year, we did not see the value of routine clinical assessment and additional follow-up radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon the nature of the health care delivery system in our city, virtually all patients initially operated upon at our institution who underwent a reoperation for their hip fracture for any reason would be treated again at our institution. It is well-recognised [1,31] that elderly patients represent a difficult patient population to return for routine follow-up. Since our only outcome measures were the immediate postoperative position of the screw or blade and reoperation and cut-out rates within the first year, we did not see the value of routine clinical assessment and additional follow-up radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Since our only outcome measures were the immediate postoperative position of the screw or blade and reoperation and cut-out rates within the first year, we did not see the value of routine clinical assessment and additional follow-up radiographs. Based upon the concept of the "Functional Recovery Score" established by Zuckerman et al [31,32], a trained medical secretary contacted each patient, family member, or other health care-giver to ascertain any change in the patient's ability to ambulate or degree of pain that might signal a failure of implant fixation. If there was any evidence of such an untoward event the patient was requested to return for evaluation and follow-up radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Para profundizar en este punto, Zuckerman (7,97) ha realizado un estudio en población sana que vive en su domicilio clasificando a los pacientes por niveles de función. Sus resultados ponen de manifiesto que, inmediatamente tras la fractura de cadera, se produce una importante pérdida de función con respecto a la situación previa, tanto para la capacidad de deambular, como para las actividades básicas y las instrumentales de la vida diaria y a partir de ese momento comienza una fase de recuperación gradual hasta los 12 meses.…”
Section: Tasa De Recuperaciónunclassified
“…Hamlet et al (1997) have reported that mortality will double in patients with postoperative complications, In addition, Sexson and Lehner (1987) have shown a 3-fold increase of mortality rates when compared to patients without postoperative complications. There is a wide spectrum of complications that may affect patients, including cardiopulmonary events, thromboembolism, bleeding, infection, delirium and pressure ulcers (Johnstone et al, 1995;McLaughlin et al, 2006;Zuckerman et al, 2000). Many studies have focused on the association between in-hospital surgical delay and the healing of the fracture (Manninger et al, 1985;Sorbie, 2003;Szita et al, 2002), and mortality in patients with a hip fracture from a quality assessment perspective (Elliott et al, 2003;Sund and Liski, 2005) and from length of stay (LOS) Siegmeth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%